(untitled) (The International Journal for Scientific Research, 2024)
This study employs the integrative design process of sustainable urban regeneration of the historical district in Sharjah city in UAE by It also improves physical and visual connectivity and integration within the neighbourhood and among the surrounding areas to encourage walkability in the district provides a liveable community, and increase accessibility and social interaction. Applying comprehensive design strategies to promote connectivity and revitalize the public places in historical district. The study employs a combination of field studies and parametric simulation tools to investigate the district and identify opportunities for improvement. By optimizing the master plan, the research aims to enhance integration and connectivity within the neighbourhood. The study yielded several significant findings; most notable was the increment of the integration value of the optimized master plan by approximately 41% in comparison with Shurooq proposed master plan 2025, as a result of improving the urban configuration, the street network enhances the connection between the old district and the waterfront, and introducing a central plaza to be connected with Al Rola park to achieve the holistic desired approach. The study’s outcomes offer practical implications for urban planners and policymakers in the Gulf Region, highlighting the importance of integrative design strategies in fostering sustainable urban regeneration and improving social interactions within historical districts. The study contributes to the promotion of sustainable urban development methods in the Gulf Region by providing insights into how to improve social interactions, promote a holistic approach to urban regeneration in historical districts, and enhance urban sustainability.